Legal obligation of the sea carrier under common law, international conventions (Hague Rules, Hague-Visby Rules and Hamburg Rules) and Iraqi law : a comparison study - Homdon, Amru K. (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2013)
Carrier obligations are among the main issues highlighted in the 1924 Hague Rules. It compels the signatory countries to protect the maritime carrier. Following the new amendments to the Hague-Visby 1968 and Hamburg 1978, the researcher found that the laws initiated by the countries that have signed the Convention, including Iraq, agreed with the content of the Hamburg Rules of 1978. Furthermore, the researcher provided a historical overview on the transport of goods by sea within the framework of the case law. The discussion highlights the carrier's obligations, responsibilities and limitation of liability for damaged goods in comparison to International Conventions and Iraqi Transport Law No. 80 of 1983. The findings of this study were discussed in-depth, followed by recommendations for further studies in Chapter Five. The researcher suggests an in-depth study to emphasize different aspects of domestic laws and International Conventions concerning the transport of goods by sea.